Academic integrity and referencing: Whose responsibility is it? - Marsh, Jennifer Dawn; Campion, Jennifer (Journal of Academic Language and Learning, 2018)
When incidents of alleged plagiarism occur, the responsibility for maintaining and upholding academic integrity is often perceived to lie with students. Consequently, there may be insufficient recognition that faculty staff, learning advisors and librarians all contribute to educating students about the fundamental competencies and values of academic scholarship, including citation and referencing expectations. In this paper, we share insights gained from a collaboration aimed at raising the standard of student writing and embedding the core values and practices associated with academic integrity into a legal writing module contained within a compulsory first year law paper that focused on research skills. The collaboration arose as a result of a formal disciplinary process that sought to address the high incidence of alleged plagiarism in a second year law paper for which the first year paper was considered to be a sufficient foundation. This resulted in workshops and open educational resources being developed to address the learning needs of current and future students, specifically with regard to paraphrasing, summarising and quotation strategies. In this paper, we outline why new relationships and resources were created. We also explain how student feedback informed the development of videos and digital content that were shared via an open wiki to improve learning opportunities in a Bachelor of Laws degree programme.